The predictive utility of the plant phylogeny in identifying sources of cardiovascular drugs - Emily Guzman; Jeanmaire Molina (Taylor & Francis Group, 2018)
Context: Cardiovascular disease (CVD) is the number one cause of death globally, responsible for over 17 million (31%) deaths in the world. Novel pharmacological interventions may be needed given the high prevalence of CVD. Objective: In this study, we aimed to find potential new sources of cardiovascular (CV) drugs from phylogenetic and pharmacological analyses of plant species that have experimental and traditional CV applications in the literature. Materials and methods: We reconstructed the molecular phylogeny of these plant species and mapped their pharmacological mechanisms of action on the phylogeny. Results: Out of 139 plant species in 71 plant families, seven plant families with 45 species emerged as phylogenetically important exhibiting common CV mechanisms of action within the family, as would be expected given their common ancestry: Apiaceae, Brassicaceae, Fabaceae, Lamiaceae, Malvaceae, Rosaceae and Zingiberaceae. Apiaceae and Brassicaceae promoted diuresis and hypotension; Fabaceae and Lamiaceae had anticoagulant/thrombolytic effects; Apiaceae and Zingiberaceae were calcium channel blockers. Moreover, Apiaceae, Lamiaceae, Malvaceae, Rosaceae and Zingiberaceae species were found to possess anti-atherosclerotic properties. Discussion and conclusions: The phylogeny identified certain plant families with disproportionately more species, highlighting their importance as sources of natural products for CV drug discovery. Though there were some species that did not show the same mechanism within the family, the phylogeny predicts that these species may contain undiscovered phytochemistry, and potentially, the same bioactivity. Evolutionary pharmacology, as applied here, may guide and expedite our efforts in discovering sources of new CV drugs.